2020
DOI: 10.1177/2050312120922027
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative admission to paediatric intensive care after tonsillectomy

Abstract: Objectives: To review interventions required by children admitted for intensive care management following tonsillectomy or adenotonsillectomy either as elective or unplanned admission in a tertiary children’s hospital. Methods: A retrospective chart review over a 10-year period between April 2007 and March 2017 was performed. Charts were interrogated for treatments that were administered in the paediatric intensive care unit. Respiratory support therapies such as supplemental oxygen administration, high-flow n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Past studies of children with pretonsillectomy PSG have demonstrated that rates of severe postoperative respiratory complications range widely, from <1% to 60%. The wide range of estimates is due to differences in the definition of respiratory events and the samples studied 3,5,7,10,11,14,15,25,27,38‐42 . Studies with estimates at the lower end of the range used more stringent definitions of SRE within a more inclusive sample of high and low‐risk patients, while those at the upper end reported on both major and minor SRE within higher‐risk patients (eg, only those with severe OSA or only those admitted to the PICU postoperatively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies of children with pretonsillectomy PSG have demonstrated that rates of severe postoperative respiratory complications range widely, from <1% to 60%. The wide range of estimates is due to differences in the definition of respiratory events and the samples studied 3,5,7,10,11,14,15,25,27,38‐42 . Studies with estimates at the lower end of the range used more stringent definitions of SRE within a more inclusive sample of high and low‐risk patients, while those at the upper end reported on both major and minor SRE within higher‐risk patients (eg, only those with severe OSA or only those admitted to the PICU postoperatively).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The reported frequency of post-AT respiratory events ranges widely, from <1% to nearly 60%, depending on the definition of events and population studied. [3][4][5][6][7][8][9][10][11][12][13][14] Some children can safely undergo outpatient AT, whereas others require inpatient observation to monitor for postoperative respiratory events. Some children are admitted to the pediatric intensive care unit (PICU) after AT due to perceived increased risk for severe respiratory events (SRE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As PICU LOS hours was not recorded in the original dataset, a conservative estimate of 24 h was used based upon existing research by Levi et al who reports 72.8% of children are discharged to the ward within 24 h following PICU admission post-AT. 37 Applied to a vulnerable paediatric population, increased oximetry costs must be balanced against economic and non-economic costs of the alternative. As Australia reports high rates of paediatric tonsillectomy in regional areas, 38 cost of regional inter-hospital transfer may be higher than in metropolitan settings.…”
Section: Discussionmentioning
confidence: 99%
“…As PICU LOS hours was not recorded in the original dataset, a conservative estimate of 24 h was used based upon existing research by Levi et al . who reports 72.8% of children are discharged to the ward within 24 h following PICU admission post‐AT 37 …”
Section: Discussionmentioning
confidence: 99%